2010
DOI: 10.1002/pssc.200983399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grain size on reactive diffusion between titanium and aluminium

Abstract: The aim of this paper was to examine the effect of titanium substrate structure refinement (to the nanometric scale) on the chemical and phase composition of Ti‐Al intermetallic layers. The material examined in the study was commercially available pure titanium with average grain size of 65 μm and 60 nm. The aluminium layer with thickness of 5 μm were obtained on both substrates using magnetron sputtering technique. After annealing more phase from Ti – Al system on nano‐crystalline titanium were observed compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…For instance, Charlot et al [ 59 ] showed that the mechanical milling process applied before the self-propagating high-temperature syntheses (SHS) process markedly decreased the ignition temperature (≈100 °C) of the reaction in Fe and Al powder mixtures, and a nanostructured Fe–Al intermetallic compound was synthesized after the reaction. Meanwhile, more phases from a Ti–Al system were observed on a nanocrystalline Ti substrate with Al layer with respect to a microcrystalline substrate by Wiecinski et al [ 60 ]. The intermetallic layer synthesized on the nanocrystalline Ti substrate was thicker and more homogeneous at 600 °C.…”
Section: Reviewmentioning
confidence: 99%
“…For instance, Charlot et al [ 59 ] showed that the mechanical milling process applied before the self-propagating high-temperature syntheses (SHS) process markedly decreased the ignition temperature (≈100 °C) of the reaction in Fe and Al powder mixtures, and a nanostructured Fe–Al intermetallic compound was synthesized after the reaction. Meanwhile, more phases from a Ti–Al system were observed on a nanocrystalline Ti substrate with Al layer with respect to a microcrystalline substrate by Wiecinski et al [ 60 ]. The intermetallic layer synthesized on the nanocrystalline Ti substrate was thicker and more homogeneous at 600 °C.…”
Section: Reviewmentioning
confidence: 99%